Avaliação de filtros eletromagnéticos e sintonizados LC para minimização de correntes de seqüência zero em sistemas de distribuição a quatro fios - Ribeiro, Nilo Sérgio Soares (2007)
The power quality appears as an important area of interest of customers and the power utilities. The increase of this interest it is explained by the improvement of the legislation pertinent to this area and the level of clarification of the customers, they are each time more conscientious of yours rights. By the power quality subject, the harmonic distortion are had as one of itens of great concern, due to the amount of no linear loads connected to the system, and the level of sensitivity of the equipment submitted to this disturbs. In this context, the present document shows the operational principle, modeling, computational implementation and performance studies of the filters for to minimize of the zero sequence current flow in the three-phase four-wire distribution systems. This research contemplates the analysis of five structures with different philosophies. The study was developed with assist of the Electromagnetic Transient Program - ATP/EMTP, where a real distribution system was modeled, presenting the same levels of harmonic distortions observed in measurements in the phases wire, and the neutral conductor of the power transformer in the real substation.